Procesy modernizacji w państwach regionu Morza Bałtyckiego - Tomala, Magdalena (Eastern Review, 2018)
This paper analyses the issue of convergence in the Baltic Sea Region countries and tries to assess the effect of economic transformation during the period of 90s in 20th century on the process of convergence. In other words it will consider whether the integration process in the European Union pulled the economies of the organization together or pushed them apart. It will analyse the most important macroeconomic data to establish the relationships between counties in the Baltic Sea Region.